DETERMINANTS OF LIFE EXPECTANCY AT BIRTH: A PANEL DATA STUDY OF LOW-MIDDLE INCOME COUNTRIES OF ASIA - Sharma, Ruchi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The objective of this investigation is to ascertain the impact of a variety of socioeconomic determinants on life expectancy in 18 low-income countries in Asia from 2005 to 2021. The coefficients were determined using the panel corrected standard errors and feasible generalised least square method. Life expectancy is significantly influenced by mortality due to non-communicable diseases, neonatal mortality rate, fertility rate, and availability of physicians. Urbanization and age dependency were deemed to be insignificant when determining life expectancy. The life expectancy can be increased by the implementation of appropriate policies that assure a reduced infant mortality rate, a higher employment rate, early diagnosis, prevention, and treatment of cancer and cardiovascular diseases.